Dynamic gesture vocabulary design for intuitive human-robot dialog - Bodiroža, Saša; Stern, Helman I.; Edan, Yael (2012 7th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2012)
This paper presents a generalized method for the design of a gesture vocabulary (GV) for intuitive and natural two-way human-robot dialog. Two GV design methodologies are proposed; one for a robot GV (RGV) and a second for a human GV (HGV). The design is based on motion gestures exerted from a cohort of subjects in response to a set of tasks needed to execute several robot waiter (RW)-customer dialogs. Using a RW setting as a case study, preliminary experimental results indicate the unique nature of the HGV obtained.